VD_FINDINFO HC / 2011 / 46 vom 26. November 2010 - VD Tribunal cantonal (2010)
CONSTATATION DES FAITS, TORT MORAL, FIXATION DE LA PEINE, PEINE PRIVATIVE DE LIBERTÉ | 49 al. 1 CO, 187 ch. 1 CP, 47 CP, 367 CPP, 411 let. g CPP, 411 let. h CPP, 411 let. i CPP, 415 CPP